Gender diversity in Indonesia: Sexuality, Islam and queer selves - Davies, Sharyn Graham (Women in Asia series / Asian Studies Association of Australia, 2010)
1. Framing place and process -- 2. Contextualizing gender -- 3. Queer(y)ing transgender -- 4. Gendering the present past -- 5. Gendering life -- 6. Calalai subject positions -- 7. Calabai subject positions -- 8. Bissu subject positions -- 9. Conclusion.